The micro leadership strategy of the principal to implementing character education in elementary school - Dike, Daniel; Parida, Lusila (Jurnal Prima Edukasia, 2020)
The micro strategy of school principal leadership within the implementation of character education for elementary school degree is very decisive for the successful development and empowerment of character values in the elementary school degree. With reference to the statement, the objective of the present study is to map the description that has been related to the micro strategy management of the school principal within the implementation of the character education for the elementary school degree. Thus, the design that has been adopted is the case study and the data for the case study are gathered from the primary sources, namely school principal, teachers, and students, through interview, observation, and documentation study in relation to the leadership management within the implementation of the character education for the elementary school degree. During the study, after the data had been gathered the data were analysed by using the Miles & Huberman Inductive Analysis. The results of the study show that the micro strategy of the school principal leadership in the Sekolah Dasar Negeri 07 Sintang have been focused on four aspects namely: (1) the reinforcement of literacy as the efforts of brightening the students’ life; (2) the learning intervention as the effort of improving the students’ discerning quality and characters; (3) the program of Ant Operation as the efforts of habitualizing the healthy, clean, and environmental-friendly life pattern; and (4) the extracurricular programs as the efforts of developing the students’ special capacities, talents, and interests. In order that the four aspects are kept assured and improved, the elementary school should deepen and expand the concept and the coverage of the literacy, improve the capacity of leading practice and teaching practice through the blended learning model, and improve the capacity of the school management system through the integrative manner in the quality system and service.